2007
DOI: 10.1016/j.cmet.2007.11.004
|View full text |Cite
|
Sign up to set email alerts
|

FoxO3 Coordinately Activates Protein Degradation by the Autophagic/Lysosomal and Proteasomal Pathways in Atrophying Muscle Cells

Abstract: Muscle atrophy occurs in many pathological states and results primarily from accelerated protein degradation and activation of the ubiquitin-proteasome pathway. However, the importance of lysosomes in muscle atrophy has received little attention. Activation of FoxO transcription factors is essential for the atrophy induced by denervation or fasting, and activated FoxO3 by itself causes marked atrophy of muscles and myotubes. Here, we report that FoxO3 does so by stimulating overall protein degradation and coor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

60
1,288
6
19

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,307 publications
(1,373 citation statements)
references
References 53 publications
60
1,288
6
19
Order By: Relevance
“…The Akt/FoxO3 pathway has been involved in both autophagic and proteasomal degradation pathways in skeletal muscle 42. FoxO3 activation drives the expression of key autophagic genes such as LC3, Bnip‐3, and Gabarap1 43. However, we have previously reported that adjuvant‐induced arthritis does not change Akt or FoxO3 phosphorylation in gastrocnemius,44 suggesting no involvement of this mechanism in activating autophagy or atrogene up‐regulation in gastrocnemius.…”
Section: Discussionmentioning
confidence: 77%
“…The Akt/FoxO3 pathway has been involved in both autophagic and proteasomal degradation pathways in skeletal muscle 42. FoxO3 activation drives the expression of key autophagic genes such as LC3, Bnip‐3, and Gabarap1 43. However, we have previously reported that adjuvant‐induced arthritis does not change Akt or FoxO3 phosphorylation in gastrocnemius,44 suggesting no involvement of this mechanism in activating autophagy or atrogene up‐regulation in gastrocnemius.…”
Section: Discussionmentioning
confidence: 77%
“…We also analysed whether urolithin B was capable of repressing the autophagy–lysosomal pathway, which is another important proteolytic pathway in muscle regulated by mTORC1 and FoxOs as well 23, 24. No markers of autophagy that we studied were changed in the presence of urolithin B.…”
Section: Resultsmentioning
confidence: 99%
“…Sandri et al reported the role for lysosome activity in muscle degradation during cancer cachexia. Actually, activation of FoxO3 stimulates lysosomal proteolysis in muscle by inducing the expression of autophagy‐related genes 46. It has been recently shown that autophagy plays a relevant role even in cancer cachexia 47.…”
Section: Resultsmentioning
confidence: 99%